Efficacy and safety of oral minoxidil in female androgenetic alopecia. Issue 6 (14th September 2020) - Vastarella, Maria; Cantelli, Mariateresa; Patrì, Angela; Annunziata, Maria Carmela; Nappa, Paola; Fabbrocini, Gabriella
Abstract: Oral minoxidil (OM) has been reported to be effective for androgenetic alopecia (AGA). In this retrospective study, we share our experience of using OM for >24 weeks in 12 patients with female AGA (Ludwig scale I‐3‐III). Twelve women (aged 18‐66 years; mean age 36.66 ± 18.79 years) with AGA (Ludwig scale I‐3‐III) were recruited. The starting dose of minoxidil was 0.50 mg daily; at 3 months, the dose was increased to 1.50 to 2 mg daily. Efficacy outcome measures were evaluated at baseline and after 24 weeks and included global clinical photography, quantitative digital videotrichoscopic assessment and quality‐of‐life evaluation. An overall improvement of 38% and 23% in hair density in the frontal and vertex area, respectively, was observed after 24 weeks. The quantitative digital videotrichoscopic evaluation highlighted a statistically significant improvement in the frontal area of the total average hair density and of the total number of hairs per unit area at 24 weeks (131.47 ± 36.11 vs 181.40 ± 57.38; P = .025 and 118.72 ± 32.61 vs 163.81 ± 51.82; P = .025, respectively). In conclusion, OM was effective and had an acceptable safety profile in treating female AGA. The low number of patients and retrospective design of this study are limitations.